Antiapoptotic and Antioxidant Properties of Orthosiphon stamineus Benth (Cat's Whiskers): Intervention in the Bcl-2-Mediated Apoptotic Pathway. (30th December 2010) - Abdelwahab, Siddig Ibrahim; Mohan, Syam; Mohamed Elhassan, Manal; Al-Mekhlafi, Nabil; Mariod, Abdelbasit Adam; Abdul, Ahmad Bustamam; Abdulla, Mahmood Ameen; Alkharfy, Khalid M.
Abstract : Antiapoptotic and antioxidant activities of aqueous-methanolic extract (CAME) of Orthosiphonstamineus Benth(OS), and its hexane (HF), chloroform (CF), n -butanol (NBF), ethyl acetate (EAF) and water (WF) fractions were investigated. Antioxidant properties were evaluated using the assays of Folin-Ciocalteu, aluminiumtrichloride, β -carotene bleaching and DPPH. The role of OS against hydrogen peroxide induced apoptosis on MDA-M231 epithelial cells was examined using MTT assay, phase contrast microscope, colorimetric assay of caspase-3, western blot and quantitative real-time PCR. Results showed that EAF showed the highest total phenolic content followed by CAME, NBF, WF, CF and HF, respectively. Flavonoid content was in the order of the CF > EAF > HF > CAME > NBF > WF. The IC50 values on DPPH assay for different extract/fractions were 126.2 ± 23, 31.25 ± 1.2, 15.25 ± 2.3, 13.56 ± 1.9, 23.0 ± 3.2, and 16.66 ± 1.5 μ g/ml for HF, CF, EAF, NBF, WF and CAME, respectively. OSreduced the oxidation of β -carotene by hydroperoxides. Cell death was dose-dependently inhibited by pretreatment with OS. Caspase-3 and distinct morphological features suggest the anti-apoptotic activities of OS. This plant not only increased the expression of Bcl-2, but also decreased Bax expression, and ultimately reduced H2 O2 -induced apoptosis. The current results showed that phenolics may provide health and nutritional benefits.